Sistem Informasi Koperasi pada PT.Intercallin Surabaya - Kania Putri Rahardjo; Lily Puspa Dewi; Adi Wibowo (Jurnal Infra, 2017)
Current condition, cooperative PT. Intercallin Surabaya has a program to manage the operations of the cooperative. The program has the disadvantage that can not be changed to meet the needs of the cooperative in accordance with the results of the meeting members of the cooperative because it has been locked out of the central IT division, for example, the percentage of savings and credit cooperatives. Moreover, in the current program has not been able to synchronize to the stock of physical goods with the system, thus affecting the stock taking process. To answer these problems required a new cooperative information systems.HTML5 web-based information systems and PHP is built using Bootstrap framework and MySQL database. Features provided include: lending money, borrowing items, setting a percentage of the interest savings and loans, purchasing, sales, card stock, and the form of PDF reports.The end result of making this information system is the user can determine the amount of the stock of goods, the percentage savings can be changed in accordance with the results of the meeting members of the cooperative, and gets reports required for managers of cooperatives. From the questionnaire results are 100% on the assessment of the application look good, 100% in ratings features both savings and loans, and 100% on an overall assessment of the problem either.